Design of a Participatory Organizational-Level Work Stress Prevention Approach in Primary Education - Bakhuys Roozeboom, Maartje C.; Niks, Irene M. W.; Schelvis, Roosmarijn M. C.; Wiezer, Noortje M.; Boot, Cécile R. L. (Frontiers in Psychology, 2022)
Background Work stress is a serious problem in primary education. Decades of research underline the importance of participatory, organizational-level work stress prevention approaches. In this approach, measures are planned to tackle causes of work stress in a participatory manner and implemented by a working group consisting of members of the organization. This approach can only be effective if the measures contain effective ingredients to decrease work stress risks and are successfully implemented. The aim of this paper is to present an outline of a work stress prevention approach that is evaluated in primary education. To ensure the appropriateness of measures, a logic model of change is built as part of the risk assessment to facilitate the selection of appropriate measures. Progression on target behaviors as well as implementation factors are real-time monitored during implementation and fed back to the working groups, to provide the opportunity to adjust action plans when needed to optimize implementation. Methods The approach consists of five steps: (1) preparation: installing an advisory board and working groups, (2) risk assessment: inventory of work stress risks (questionnaires and focus groups). In addition, a behavioral analysis is performed to build a logic model of change to facilitate selection of measures, (3) action planning: conducting an action plan with appropriate measures (focus groups), (4) implementation: implementing the action plan. During implementation progression on target behaviors and implementation factors are monthly monitored and fed back to the working groups, and (5) evaluation: effects of the approach are studied in a controlled trial with measurements at baseline (T0), 1 year (T1), and 2 years (T2) follow-up. A process evaluation is carried out using quantitative (questionnaires and real-time monitoring data) and qualitative (interviews and data logs) data to study the implementation process of all steps of the work stress approach. Discussion We believe that building a logic model of change and real-time monitoring of implementation could be of added value to improve the success of the work stress prevention approach. With this study, we aim to provide more insights into work stress intervention research, especially in primary education. Clinical Trial Registration The study is registered in Netherlands Trial Register (ClinicalTrials.gov #NL9797, October 18, 2021).